Composite conductive filler particles, conductive resin composition, and conductive resin molded article

By covering amorphous carbon on the graphite particles to form composite conductive filler particles, the problems of reduced strength of the conductive resin composition and poor gas permeability caused by graphite particles in the resin material are solved, and a conductive resin composition with high conductivity and strength is realized, which is suitable for the manufacturing of high-performance molded bodies.

CN119790018APending Publication Date: 2025-04-08MITSUBISHI PENCIL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380062524.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The conductive resin composition in which graphite particles are added as conductive fillers is added to the resin material, and the peeling at the interface between the resin material and the graphite particles and the cleavage of the graphite particles themselves leads to a decrease in strength and poor gas permeability.

Method used

By covering the graphite particles with amorphous carbon, composite conductive filler particles are formed, and peeling at the interface between the resin material and the graphite particles and cleavage of the graphite particles themselves are suppressed, thereby improving the strength and gas opacity of the conductive resin composition.

Benefits of technology

The conductive resin composition with high conductivity, high strength and excellent gas opacity is achieved, and is suitable for the production of high-performance conductive resin composition molded bodies, such as a fuel cell separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790018A_ABST
    Figure CN119790018A_ABST
Patent Text Reader

Abstract

The present invention provides: composite conductive filler particles (10) having graphite particles (2) and amorphous carbon (1) covering the graphite particles; a conductive resin composition (20) having a resin material (3) and the composite conductive filler particles (10) dispersed in the resin material (3); and a conductive resin composition molded article comprising the molded conductive resin composition (20).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to composite conductive filler particles, a conductive resin composition and a conductive resin composition molded body. Background Art

[0002] Conductive resin compositions are required in various fields, and such resin compositions are generally obtained by incorporating a conductive filler such as carbon particles, carbon fibers, metal particles, or conductive metal oxide particles into a resin material.

[0003] In this regard, for example, Patent Document 1 proposes the use of a conductive resin composition to manufacture a circuit substrate, Patent Document 2 proposes the use of a conductive resin composition to manufacture a resin collector for a lithium ion battery, and Patent Document 3 proposes the use of a conductive resin composition to manufacture an electromagnetic wave shield. In addition, Patent Document 4 discloses a separator for a fuel cell, characterized in that a conductive gas blocking layer (B) is provided on a conductive layer (A) formed by bonding and curing conductive fibers with a synthetic resin.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-102442

[0007] Patent Document 2: Japanese Patent Application Publication No. 2022-085826

[0008] Patent Document 3: Japanese Patent Application Publication No. 2021-161193

[0009] Patent Document 4: Japanese Patent Application Publication No. 2001-015131 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] When a conductive resin composition is obtained by incorporating carbon particles as a conductive filler into a resin material, it is preferred to add a large amount of highly conductive carbon particles, ie, graphite particles, as a conductive filler to the resin material in order to impart high conductivity to the conductive resin composition.

[0012] However, the inventors of the present application have found that a conductive resin composition in which graphite particles are added to a resin material as a conductive filler has a trade-off problem in quality, such as a decrease in the strength of the conductive resin composition and a decrease in gas permeability, due to delamination at the interface between the resin material and the graphite particles and cleavage of the graphite particles themselves.

[0013] The present invention provides a conductive resin composition having high conductivity and high strength and / or excellent gas impermeability, a conductive filler used for such a conductive resin composition, and a conductive resin composition molded body produced from such a conductive resin composition.

[0014] Solutions for solving problems

[0015] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by the following means, thereby completing the present invention. That is, the present invention is as follows.

[0016] <Method 1>

[0017] A composite conductive filler particle comprises graphite particles and amorphous carbon coating the graphite particles.

[0018] <Method 2>

[0019] The composite conductive filler particles according to Embodiment 1 have a volume average diameter of 5 μm to 1000 μm.

[0020] <Method 3>

[0021] The composite conductive filler particles according to aspect 1, wherein the ratio of the graphite particles to the total of the amorphous carbon and the graphite particles is 10% by mass to 95% by mass.

[0022] <Method 4>

[0023] The composite conductive filler particles according to Embodiment 1, wherein the volume average diameter of the graphite particles is 1 μm to 500 μm.

[0024] <Method 5>

[0025] A conductive resin composition comprises a resin material and the composite conductive filler particles according to embodiment 1 dispersed in the resin material.

[0026] <Method 6>

[0027] The conductive resin composition according to Embodiment 5, wherein the ratio of the composite conductive filler particles to the total of the resin material and the composite conductive filler particles is 5% by mass to 95% by mass.

[0028] <Method 7>

[0029] A conductive resin composition molded body, comprising the conductive resin composition molded in aspect 5.

[0030] <Method 8>

[0031] The conductive resin composition molded article according to Embodiment 6, which is in a sheet shape.

[0032] <Method 9>

[0033] The conductive resin composition molded article according to Embodiment 7 is a separator for a fuel cell.

[0034] <Method 10>

[0035] A method for producing a conductive resin composition molded body according to embodiment 7, comprising: providing a mixture comprising thermoplastic resin fibers and the composite conductive filler particles according to embodiment 1 dispersed between the resin fibers,

[0036] The mixture is heated and pressurized to be molded.

[0037] <Method 11>

[0038] The method according to embodiment 10, wherein the mixture includes a fiber molded body composed of the resin fibers and the composite conductive filler particles dispersed between the resin fibers in the fiber molded body, and the mixture is molded by heating and pressurizing.

[0039] Effects of the Invention

[0040] According to the present invention, there are provided a conductive resin composition having high conductivity and high strength, a conductive filler used for such a conductive resin composition, and a conductive resin composition molded body produced from such a conductive resin composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The composite conductive filler particles of the present invention ( Figure 1 (a)) and a conductive resin composition of the present invention containing the composite conductive filler particles of the present invention ( Figure 1 (b) is a schematic cross-sectional view of the method.

[0042] Figure 2 It is a graphite filler particle ( Figure 2 (a)) and a conventional conductive resin composition containing conventional graphite filler particles ( Figure 2 (b) is a schematic cross-sectional view of the method. DETAILED DESCRIPTION

[0043] 《Composite conductive filler particles》

[0044] The composite conductive filler particles of the present invention include graphite particles and amorphous carbon coating the graphite particles.

[0045] As described above, in order to impart high conductivity to the conductive resin composition, it is preferred to add a large amount of graphite particles to the resin material. However, as described above, the conductive resin composition having graphite particles added to the resin material has a trade-off problem in that the strength of the conductive resin composition is reduced and gas permeation is poor due to peeling at the interface between the resin material and the graphite particles and cleavage of the graphite particles themselves.

[0046] In contrast, in the composite conductive filler particles of the present invention, since the graphite particles are coated with amorphous carbon, problems caused by peeling at the interface between the resin material and the graphite particles and cleavage of the graphite particles themselves can be suppressed, and the high conductivity of the graphite particles can be utilized.

[0047] Here, the presence of amorphous carbon on the surface of the conductive filler of the present invention can be confirmed by the D-band (1100 to 1450 cm -1 ) and G-band (1450~1700cm -1 ) is confirmed by being greater than or equal to 0.5, particularly greater than or equal to 0.5 and less than or equal to 1.1. It should be noted that this ratio is less than 0.5 when only graphite is present, and is greater than 1.1 when only amorphous carbon is present. Therefore, it is believed that the ratio is greater than or equal to 0.5 and less than 1.1 because the amorphous carbon layer on the surface is thin or there are gaps in the amorphous carbon layer on the surface, thereby obtaining a spectrum based on a bond derived from graphite together with a spectrum based on a bond derived from amorphous carbon.

[0048] The graphite particles contained in the composite conductive filler particles of the present invention may be in any form such as flaky, spherical, massive, or flake-like graphite particles, but flaky or spherical graphite particles are preferably used from the viewpoint of conductivity.

[0049] Such composite conductive filler particles of the present invention may be, for example, Figure 1 That is, as shown in (a) of Figure 1 As shown in (a), the composite conductive filler particles 10 of the present invention include graphite particles 2 and amorphous carbon 1 covering the graphite particles 2. Figure 1 As shown in (b), by adding the composite conductive filler particles 10 of the present invention to the resin material 3, a conductive resin composition 20 can be obtained.

[0050] In contrast, graphite particles such as Figure 1As shown in (b), the graphite particles 2 are separated, and the conventional conductive resin composition 30 is obtained by adding such separated graphite particles 2 to the resin material 3. As described above, such conventional conductive resin composition 30 sometimes has problems caused by the peeling portion 2a at the interface between the resin material 3 and the graphite particles 2 and the cleavage portion 2b of the graphite particles 1 themselves. Such conventional conductive resin composition 30 sometimes has the following problem: the conductive resin composition becomes easy to break due to these peeling portions 2a and cleavage portions 2b.

[0051] The volume average diameter of the composite conductive filler particles of the present invention may be 5 μm to 1000 μm. The volume average diameter may be 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or less, 900 μm or less, 800 μm or less, 700 μm or less, 600 μm or less, 500 μm or less, 400 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, or 100 μm or less.

[0052] Here, the "volume average diameter" (Mv) of the present invention can be obtained by dividing the weighted average value of the product of the frequency of each particle size and the respective volume calculated using the particle size by the average volume using a laser diffraction particle size distribution measuring apparatus (e.g., MT-3000 manufactured by Microtrac BEL Co., Ltd.) by the average volume.

[0053] In the composite conductive filler particles of the present invention, the ratio of graphite particles can be 10% to 95% by mass relative to the total of amorphous carbon and graphite particles. In order to cover the graphite particles with amorphous carbon, it is preferred that the ratio is small to suppress the peeling at the interface between the resin material and the graphite particles and the cleavage of the graphite particles themselves. On the other hand, in order to utilize the good conductivity of the graphite particles, it is preferred that the ratio is large. The ratio can be 10% by mass or more, 20% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, or 70% by mass or more, and can also be 95% by mass or less, 90% by mass or less, 85% by mass or less, or 80% by mass or less.

[0054] Here, the "ratio of graphite particles relative to the total of amorphous carbon and graphite particles" of the present invention can be calculated based on the weight ratio of various raw materials in the production stage of the composite conductive filler particles of the present invention and the residual rate after firing (carbon yield), with the residual rate of the graphite particles used being set to 100% by mass.

[0055] In the composite conductive filler particles of the present invention, the volume average diameter of the graphite particles dispersed in the amorphous carbon may be 1 μm to 500 μm. In addition, the volume average diameter of the graphite particles may be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 7 μm or more, 10 μm or more, 15 μm or more, 25 μm or more, or 30 μm or less, 500 μm or less, 400 μm or less, 370 μm or less, 350 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less.

[0056] The composite conductive filler particles of the present invention can be manufactured by any method. For example, graphite particles are dispersed in a resin material to obtain a resin block containing graphite particles in which graphite particles are dispersed in the resin material, the resin block containing graphite particles is arbitrarily solidified and / or infusible, and then fired in an inert gas atmosphere, the resin material is amorphously carbonized to obtain an amorphous carbon block containing graphite particles, and the amorphous carbon block containing graphite particles is crushed and arbitrarily classified to obtain the composite conductive filler particles of the present invention. It should be noted that regarding the method of dispersing graphite particles in a resin material, reference can be made to the following description related to the method for manufacturing a conductive resin composition.

[0057] It should be noted that, as the resin used here to be amorphously carbonized, any thermoplastic resin and curable resin that are amorphously carbonized when fired in an inert gas atmosphere can be used. As thermoplastic resins, for example, thermoplastic polyimide resin (TPI), chlorinated vinyl chloride resin (CPVC), polyvinyl chloride resin (PVC), polyetherimide resin (PEI) or polyacrylonitrile resin (PAN) can be cited, but it is not limited to these. In addition, as thermosetting resins, for example, polyimide resins, furan resins or phenolic resins can be cited, but it is not limited to these.

[0058] 《Conductive resin composition》

[0059] The conductive resin composition of the present invention comprises a resin material and the composite conductive filler particles of the present invention dispersed in the resin material.

[0060] As described above, according to such a conductive resin composition, it is possible to suppress the peeling at the interface between the resin material and the graphite particles and the problems caused by the cleavage of the graphite particles themselves, and to utilize the high conductivity of the graphite particles.

[0061] The ratio of the composite conductive filler particles to the total of the resin material and the composite conductive filler particles may be 5% to 95% by mass. The ratio may also be 5% by mass or more, 10% by mass or more, 20% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, or 70% by mass or less, or 95% by mass or less, 90% by mass or less, 80% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less.

[0062] The conductive resin composition of the present invention may contain any additional components other than the resin material and the composite conductive filler particles. Examples of such additional components include glass-based materials such as glass fibers; cellulose-based materials such as carboxymethyl cellulose and cellulose nanofibers; and carbon-based materials such as carbon fibers, graphite, graphene, carbon nanotubes, carbon black, acetylene black, and Ketjen black. In order to provide the conductive resin composition of the present invention with high conductivity, it is sometimes preferred to contain carbon fibers as an additional component.

[0063] The conductive resin composition of the present invention can be produced by any method, and can be produced by any known method for obtaining a conductive resin composition in which a conductive filler is dispersed in a resin material. Therefore, for example, the conductive resin composition of the present invention can be produced by the following method:

[0064] (i) mixing a powdery or fibrous resin material with the composite conductive filler particles of the present invention, and heating and optionally pressing the resulting mixture,

[0065] (ii) mixing a liquid curable resin with the composite conductive filler particles of the present invention, heating and optionally pressing the resulting mixture, or placing it in a mold to cure the curable resin,

[0066] (iii) kneading a thermoplastic resin material melted or softened by heating with the composite conductive filler particles of the present invention, or

[0067] (iv) A fiber molded product composed of thermoplastic resin fibers, such as a sheet-like fiber molded product such as a nonwoven fabric, is impregnated with a dispersion containing the composite conductive filler particles of the present invention, the dispersion medium is removed, and the obtained fiber molded product is then heated and optionally pressed.

[0068] 《Conductive resin composition molded body》

[0069] The conductive resin composition molded body of the present invention is composed of the molded conductive resin composition of the present invention. The conductive resin composition molded body can have any shape depending on the application, for example, it can be a sheet. In addition, the conductive resin composition molded body can be a separator for a fuel cell. The conductive resin composition molded body has high conductivity and high strength, and therefore can be preferably used as a separator for a fuel cell.

[0070] The conductive resin composition molded body of the present invention can be produced by any method, and can be produced by any known method for obtaining a conductive resin composition molded body in which a conductive filler is dispersed in a resin material. Therefore, for example, the conductive resin composition molded body of the present invention can be produced by the following method:

[0071] (i) mixing a powdery or fibrous resin material with the composite conductive filler particles of the present invention, and heating and pressing the resulting mixture to form a mold,

[0072] (ii) mixing a liquid curable resin with the composite conductive filler particles of the present invention, and heating and pressing the obtained mixture to form a mold, or placing the mixture in a mold to cure the curable resin to form a mold,

[0073] (iii) molding the conductive resin composition of the present invention by press molding, extrusion molding, roll molding, injection molding, or the like, or

[0074] (iv) A fiber molded product composed of thermoplastic resin fibers, such as a sheet-like fiber molded product such as a nonwoven fabric, is impregnated with a dispersion containing the composite conductive filler particles of the present invention, the dispersion medium is removed, and the obtained fiber molded product is heated and pressed to form the fiber molded product.

[0075] In addition, for example, the conductive resin composition molded body of the present invention can be produced by providing a mixture containing thermoplastic resin fibers and the composite conductive filler particles of the present invention dispersed between the resin fibers, and heating and pressurizing the mixture to mold it. In this method, in particular, the mixture contains a fiber molded body composed of resin fibers (for example, a sheet-like fiber molded body, especially a nonwoven fabric or fiber paper) and the composite conductive filler particles of the present invention dispersed between the resin fibers in the fiber molded body, and the mixture is heated and pressurized to be molded, and in particular, it can be molded into a sheet.

[0076] Example

[0077] 《Examples 1 to 13》

[0078] <Preparation of Composite Conductive Filler Particles A to I>

[0079] The materials of the following composition were mixed by a Henschel mixer and placed in a kneader, and kneaded while being heated to 100° C. to melt the polyvinyl chloride resin. The obtained mixture was cooled, pulverized by a biaxial pulverizer, and then heated at 180° C. for 24 hours to prevent melting, thereby obtaining a graphite-containing resin mass.

[0080] Scaly graphite particles (volume average diameter (Mv): 5 μm): 40 mass%

[0081] Polyvinyl chloride resin: 40% by mass

[0082] Lubricating material: 1 mass%

[0083] Plasticizer: 19 mass%

[0084] The graphite-containing resin block obtained as described above was fired at 1000° C. in a nitrogen atmosphere to amorphously carbonize the polyvinyl chloride resin, thereby obtaining a graphite-containing amorphous carbon block. The graphite-containing amorphous carbon block was crushed using an alumina mortar and classified using a sieve to obtain composite conductive filler particles A. The obtained composite conductive filler particles A had a volume average diameter (Mv) of 200 μm.

[0085] It should be noted that the residual rate of the above-mentioned graphite-containing amorphous carbon block during firing is 53.33%, the residual rate of flaky graphite particles is about 100% by mass, and the residual rate of lubricating material and plasticizer is about 0% by mass. Therefore, considering the weight ratio of the raw materials, it is believed that in the composite conductive filler particles A, the proportion of graphite particles relative to the total of graphite particles and amorphous carbon is about 75% by mass.

[0086] Composite conductive filler particles B to I were prepared in the same manner as composite conductive filler particle A, except that the degree of crushing and the mesh size of the sieve used for classification were adjusted, the volume average diameter (Mv) of the obtained composite conductive filler particles was changed, flaky graphite with different volume average diameters (Mv) was used as the raw material, and spherical graphite was used as the raw material instead of flaky graphite.

[0087] The details of the composite conductive filler particles A to I are shown in Table 1 below.

[0088] [Table 1]

[0089] Table 1

[0090]

[0091] <Production of Evaluation Sheets>

[0092] Conductive resin sheets of Examples 1 to 15 were obtained using the composite conductive filler particles A to I, molding resins, and carbon fibers (except Example 1) obtained as described above. The composite conductive filler particles A to I, molding resins, and carbon fibers used were in the following ratios.

[0093] ・When carbon fiber is not used

[0094] Composite conductive filler particles A to I: 40 mass%

[0095] Molding resin: 60 mass%

[0096] ·When using carbon fiber

[0097] Composite conductive filler particles A to I: 40 mass%

[0098] Molding resin: 40% by mass

[0099] Carbon fiber used: 20 parts by mass

[0100] Specifically, when the molding resin is polyetherimide, polyphenylene sulfide or polyvinylidene fluoride, the composite conductive filler particles, the powdered molding resin and the carbon fibers as required are mixed by a mixer, and press-molded at a pressure of 10 MPa using a flat plate-shaped mold heated to 250 to 330°C to obtain a conductive sheet with a thickness of 200 to 300 μm.

[0101] When the molding resin is a resol-type phenolic resin, the composite conductive filler particles, liquid molding resin, and carbon fibers are mixed in a mixer, and press-molded at a pressure of 10 MPa using a flat plate-shaped mold heated to 250-330°C to obtain a conductive sheet with a thickness of 200-300 μm.

[0102] When the molding resin is 6-nylon, the composite conductive filler particles are added to a 0.5 mass % DEMOL N aqueous solution to a concentration of 8 mass %, and after ultrasonic dispersion, the dispersion is diluted to 2 times with ethanol to obtain a filler particle dispersion. Then, 10 times the weight of the filler particle dispersion is added dropwise to a non-woven fabric of 6-nylon containing carbon fibers, dried at 70°C, and press-molded at a pressure of 10 MPa using a flat plate-shaped mold heated to 250°C to obtain a conductive sheet with a thickness of 200 to 300 μm.

[0103] <Evaluation>

[0104] The obtained conductive sheet was measured for conductivity evaluation by measuring contact resistance, and for strength evaluation by measuring the maximum point stress obtained in a three-point bending test at a support point distance of 15 mm.

[0105] In addition, the gas permeability was measured by the differential pressure method in accordance with "JIS K7126-1: 2006" for Examples 11 to 12 and Comparative Example 8. The pressure of the test gas was set to 100 kPa (high pressure side), and nitrogen was used as the test gas.

[0106] Comparative Example 1

[0107] A conductive resin sheet of Comparative Example 1 was obtained and evaluated in the same manner as in Example 1 except that the composite conductive filler particles (containing flaky graphite particles) were not used.

[0108] Comparative Example 2

[0109] A conductive resin sheet of Comparative Example 2 was obtained and evaluated in the same manner as in Example 2, except that uncompounded flaky graphite alone was used instead of the composite conductive filler particles (containing flaky graphite particles). In Comparative Example 2, the amount of flaky graphite alone was the same as that of the composite conductive filler particles in Example 2.

[0110] 《Comparative Examples 3 and 4》

[0111] Conductive resin sheets of Comparative Examples 3 and 4 were obtained and evaluated in the same manner as in Examples 3 to 6 except that uncompounded single flaky graphite was used instead of the composite conductive filler particles (containing flaky graphite particles). In Comparative Examples 3 and 4, the amount of single flaky graphite was the same as the amount of the composite conductive filler particles in Examples 3 to 6. The volume average diameter (Mv) of the single flaky graphite used in Comparative Example 3 was 200 μm, and the volume average diameter (Mv) of the single flaky graphite used in Comparative Example 4 was 30 μm.

[0112] 《Comparative Example 5》

[0113] The conductive resin sheet of Comparative Example 5 was obtained and evaluated in the same manner as in Examples 3 to 6, except that a mixture of flaky graphite particles and amorphous carbon particles was used instead of the composite conductive filler particles (containing flaky graphite particles). It should be noted that in Comparative Example 5, the amount of the mixture of flaky graphite particles and amorphous carbon particles was the same as the amount of the composite conductive filler particles in Examples 3 to 6. The weight ratio of the flaky graphite particles and amorphous carbon particles was 3:1. In addition, the volume average diameter (Mv) of the mixture of flaky graphite particles and amorphous carbon particles used in Comparative Example 5 was 30 μm.

[0114] 《Comparative Example 6》

[0115] A conductive resin sheet of Comparative Example 6 was obtained and evaluated in the same manner as in Example 9, except that uncompounded single spherical graphite particles were used instead of the composite conductive filler particles (containing spherical graphite particles). In Comparative Example 6, the amount of the single spherical graphite particles was the same as that of the composite conductive filler particles in Example 9. The volume average diameter (Mv) of the single spherical graphite particles used in Comparative Example 6 was 20 μm.

[0116] Comparative Examples 7 to 11

[0117] Conductive resin sheets of Comparative Examples 7 to 11 were obtained and evaluated in the same manner as in Examples 10, 11, and 13 to 15, except that uncompounded single flaky graphite was used instead of the composite conductive filler particles (containing flaky graphite particles). In these Comparative Examples 7 to 11, the amount of single flaky graphite was the same as the amount of composite conductive filler particles in Examples 10 to 13. The volume average diameter (Mv) of the single flaky graphite used in Comparative Examples 7 and 9 to 11 was 30 μm, and the volume average diameter (Mv) of the single flaky graphite used in Comparative Example 8 was 350 μm.

[0118] The details and evaluation results of the conductive sheets of Examples and Comparative Examples are shown in Tables 2 to 9 below.

[0119] [Table 2]

[0120] Table 2

[0121]

[0122] [Table 3]

[0123] Table 3

[0124]

[0125] Table 44]

[0126] Table 4

[0127]

[0128] [Table 5]

[0129] Table 5

[0130]

[0131] [Table 6]

[0132] Table 6

[0133]

[0134] [Table 7]

[0135] Table 7

[0136]

[0137] [Table 8]

[0138] Table 8

[0139]

[0140] [Table 9]

[0141] Table 9

[0142]

[0143] As shown in Tables 2 to 9, it can be observed that the resistance value is lower when the conductive filler is added than when no conductive filler is added. In addition, it is observed that the strength is lowered when the graphite particles alone are used as the conductive filler, while these properties are better when the composite conductive filler particles of the present invention are used.

[0144] Furthermore, as shown in Table 6, when the composite conductive filler particles of the present invention are used as conductive fillers, the gas permeability is lower and the gas impermeability is good compared to the case of using graphite particles alone. Regarding Examples 1 to 10 and 13 to 15, the gas permeability was not measured, but as described above, since good strength can be obtained, it can be considered that the cleavage of the graphite particles is suppressed. Therefore, it can be predicted that these Examples can all obtain good gas impermeability.

[0145] Description of Reference Numerals

[0146] 1 Amorphous carbon

[0147] 2 Graphite particles

[0148] 2a Delamination at the interface between the resin material and the graphite particles

[0149] 2b Cleavage of graphite particles

[0150] 3. Resin material

[0151] 10 Composite conductive filler particles of the present invention

[0152] 20 Conductive resin composition of the present invention

[0153] 30 Conventional conductive resin composition

Claims

1. Composite conductive filler particles comprising graphite particles and amorphous carbon coating the graphite particles. 2 . The composite conductive filler particles according to claim 1 , wherein the volume average diameter thereof is 5 μm to 1000 μm.

3. The composite conductive filler particle according to claim 1, wherein: The ratio of the graphite particles to the total of the amorphous carbon and the graphite particles is 10% by mass to 95% by mass.

4. The composite conductive filler particle according to claim 1, wherein The volume average diameter of the graphite particles is 1 μm to 500 μm. 5 . A conductive resin composition comprising a resin material and the composite conductive filler particles according to claim 1 dispersed in the resin material.

6. The conductive resin composition according to claim 5, wherein The ratio of the composite conductive filler particles to the total of the resin material and the composite conductive filler particles is 5% by mass to 95% by mass.

7. A conductive resin composition molded body, comprising the conductive resin composition according to claim 5 molded into a molded body. The conductive resin composition molded body according to claim 6 , which is in a sheet shape. 9 . The conductive resin composition molded body according to claim 7 , which is a separator for a fuel cell.

10. A method for producing a conductive resin composition molded body according to claim 7, comprising: providing a mixture comprising thermoplastic resin fibers and the composite conductive filler particles according to claim 1 dispersed between the resin fibers, The mixture is heated and pressurized to be molded.

11. The method according to claim 10, wherein: The mixture includes a fiber molded body composed of the resin fibers and the composite conductive filler particles dispersed between the resin fibers in the fiber molded body, and the mixture is molded by heating and pressurizing.

Citation Information

Patent Citations

  • Separator for fuel cell, its manufacture, and fuel cell

    JP2001015131A

  • Conductive resin composition and electromagnetic wave-shielding material using the composition

    JP2021161193A

  • Resin current collector for lithium ion battery, and method for manufacturing the same

    JP2022085826A

  • Conductive resin composition, circuit board fabricated using the same, and method of manufacturing circuit board

    JP2022102442A